The role of host and microbial factors in the pathogenesis of chronic schistosomiasis in mice - Mpotje, Thabo Rantanta Victor (Department of Pathology, 2021)
There is burgeoning interest in the complex tripartite interplays between the commensal microbiota, host's genetic factors, and immune response during helminth infections which are still poorly understood. The study explores this relationship in the context of chronic schistosomiasis-driven pathology. In the first part of the thesis, removal of the host Basic Leucine Zipper ATF-Like Transcription Factor 2 (Batf2) gene in 129Sv (Batf2-/- ) mice resulted in alteration of the intestinal microbial composition and reduced granulomatous inflammatory immune response. These changes associated with rescue from pre-mature mortality and improved fitness of Batf2-/- mice during chronic experimental schistosomiasis in relation to control wild type mice. The prolonged survival and reduced immunopathology were diminished by treatment with α-CD8 antibody highlighting the significance of CD8-expressing immune mediators during chronic Schistosomiasis. Transfer of the altered intestinal microbiota from Batf2-/- mice to wild type mice by co-housing was enough to rescue the latter from exacerbated granulomatous inflammation and prolonged their survival during chronic schistosomiasis. These observations suggest, for the first time, a central role of the host gut microbiota in decisively regulating the tissue immune response, the elicited pathology and host survival during schistosomiasis. To validate the robustness of this tripartite interaction during chronic schistosomiasis around the gut microbiota, the second part of the present work analysed two genetically identical murine models (C57BL/6) housed under two different specific Pathogen free environments (SPF1 and SPF2) and presenting differential susceptibility to chronic schistosomiasis. Our work revealed a higher susceptibility of C57BL/6 mice from the SPF2 facility in relation to C57BL/6 mice from the SPF1 facility. In confirmation with our first series of experiments, that demonstrated a central role of the host intestinal microbiota in regulating the immune responses, the pathology, and the survival of the host during schistosomiasis, the second series of experiments further presented an ameliorated immunological, pathological and vital prognosis of vulnerable SPF2 C57BL/6 mice receiving the intestinal microbiota of more resistant SPF1 C57BL/6 mice. Therefore, the study demonstrates the genetic regulation of gut microbiota which in turn, and/or in concert with the genetic make-up, influence the immunological, pathological, and vital host response during chronic schistosomiasis. The present work expands the conventional knowledge on schistosomiasis disease regulation and presents the gene-microbiota-immune-response interactome as a core piece of the regulatory machinery of this infection as exploitable to alter disease progression in the context of drug and vaccine development.